COMPETITIVENESS OF FOOD AGRO-INDUSTRIAL MSMEs: ROLE OF BUSINESS MANAGEMENT AND GOVERNMENT POLICY - Andreastika, Kristantiya; Santoso, Imam; Deoranto, Panji (Universitas Brawijaya, Indonesia, 2017)
Â Micro, Small and Medium Enterprises (MSMEs) are the business Group that become important part in the development of the national economy, and also as strategic sector for the nation of Indonesia. The increasing of the number MSMEs is not accompanied by an increase the quality and competitiveness to face the competition from other MSMEs, many factor which influenced toward the increased of performance and competitiveness should come first, as well as reduce the problems that become obstacles the development MSMEs. The problems faced by MSMEs in Malang Regency including managerial aspect to managed business and government policies that have not fully give benefit for micro and macro business. The purpose of this research is to analyze influence of business management variables (X1) and government policies (X2) on the performance (Y1) competitiveness (Y2) food agro industrial MSMEs in Malang. The research used Partial Least Square (PLS) methodÂ toÂ analyzing the data. Respondents of this study are 30 MSMEs, who were taken using purposive sampling technique. The results showed that the variables of business management not significant effect on performance and significant effect on the competitiveness of MSMEs. Government policies have a significant effect on the performance of MSMEs and not significant effect on competitiveness. Performance of MSMEs has a significant effect on competitiveness. Variable business management provides the strongest direct influence on the competitiveness of MSMEs.